Mutations responsible for MYH9-related thrombocytopenia impair SDF-1-driven migration of megakaryoblastic cells - Pecci, Alessandro; Bozzi, Valeria; Panza, Emanuele; Barozzi, Serena; Gruppi, Cristian; Seri, Marco; Balduini, Carlo L. (Thrombosis and Haemostasis, 2011)
MYH9-related disease (MYH9-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for the heavy chain of nonmuscle myosin-IIA (NMMHC-IIA). Recent in vitro studies led to the hypothesis that thrombocytopenia of MYH9-RD derives from an ectopic platelet release by megakaryocytes in the osteoblastic areas of bone marrow (BM), which are enriched in type I collagen, rather than in vascular spaces. SDF-1-driven migration of megakaryocytes within BM to reach the vascular spaces is a key mechanism for platelet biogenesis. Since myosin-IIA is implicated in polarised migration of different cell types, we hypothesised that MYH9 mutations could interfere with this mechanism. We therefore investigated the SDF-1-driven migration of a megakaryoblastic cell line, Dami cells, on type I collagen or fibrinogen by a modified transwell assay. Inhibition of myosin-IIA ATPase activity suppressed the SDF-1-driven migration of Dami cells, while over-expression of NMMHC-IIA increased the efficiency of chemotaxis, indicat- ing a role for NMMHC-IIA in this mechanism. Transfection of cells with three MYH9 mutations frequently responsible for MYH9-RD (p.R702C, p.D1424H, or p.R1933X) resulted in a defective SDF-1-driven migration with respect to the wild-type counterpart and in increased cell spreading onto collagen. Analysis of differential localisation of wild-type and mutant proteins suggested that mutant NMMHC-IIAs had an impaired cytoplasmic re-organisation in functional cytoskeletal structures after cell adhesion to collagen. These findings support the hypothesis that a defect of SDF-1-driven migration of megakaryocytes induced by MYH9 mutations contributes to ectopic platelet release in the BM osteoblastic areas, resulting in ineffective platelet production.
Keywords: MYH9-related disease; inherited thrombocytopenia; nonmuscle myosin IIA; cell migration; MYH9 mutations